Nigraha: Machine-learning-based pipeline to identify and evaluate planet candidates from TESS. Issue 2 (27th January 2021) - Rao, Sriram; Mahabal, Ashish; Rao, Niyanth; Raghavendra, Cauligi
ABSTRACT: The Transiting Exoplanet Survey Satellite (TESS) has now been operational for a little over two years, covering the Northern and the Southern hemispheres once. The TESS team processes the downlinked data using the Science Processing Operations Center (SPOC) pipeline and Quick Look pipeline (QLP) to generate alerts for follow-up. Combined with other efforts from the community, over 2000 planet candidates have been found of which tens have been confirmed as planets. We present our pipeline, Nigraha, that is complementary to these approaches. Nigraha uses a combination of transit finding, supervised machine learning, and detailed vetting to identify with high confidence a few planet candidates that were missed by prior searches. In particular, we identify high signal-to-noise ratio shallow transits that may represent more Earth-like planets. In the spirit of open data exploration, we provide details of our pipeline, release our supervised machine learning model and code as open source, and make public the 38 candidates we have found in seven sectors. The model can easily be run on other sectors as is. As part of future work, we outline ways to increase the yield by strengthening some of the steps where we have been conservative and discarded objects for lack of a datum or two.